Variabilidade entre árvores matrizes de Ceiba speciosa St. Hil para características de frutos e sementes - Neto, Antonio Roveri [UNESP]; de Paula, Rinaldo Cesar [UNESP] (GN1 Sistemas e Publicacoes, 2017)
Ceiba speciosa St. Hil. (Malvaceae), known locally as paineira-rosa, is an arboreal species of great importance in the recovery of degraded ecosystems, and whose wood and kapok are used for various economic activities. This study evaluated variability and repeatability for the biometric characteristics of fruit and seeds, and seed quality between mother trees of C. speciosa. Fruit was collected from 36 mother trees and the diameter, length, fresh and dry weight and number of seeds in five fruit, and the length, diameter and 100-seed weight in 100 seeds were determined. The physiological quality of the seeds was evaluated by germination and by the following tests for vigour: germination speed index, accelerated ageing (EA), electrical conductivity (EC) and submersion of the seeds in water. Four replications of 25 seeds were used, except for the tests of EC and submersion, where 40 seeds were used in each replication. After the tests for EA and submersion, the seeds were submitted to the germination test. The mean values for the parent trees were compared by Scott-Knott test, and the genotypic coefficient of determination, the repeatability and correlation between characteristics were estimated. The characteristics under evaluation display significant variability between the mother trees, suffering little effect from the environment. The correlation between biometric characteristics and germination and seed quality is low. The repeatability coefficients are high, and the evaluation of five fruits and 100 seeds per mother tree, employing four replications in the tests for germination and vigour, offers good reliability for determining the variability of the species.
Variability among mother trees of Ceiba speciosa St. Hil for characteristics of the fruits and seeds